Zginanie i Wyboczenie Ram Przestrzennych Złożonych z Prętów o Zmiennych Sztywnościach Zginania i Skręcania - Krynicki, E.; Mazurkiewicz, Z. (Engineering Transactions, 1965)
Bar structures of variable flexural and torsional rigidities find wide application in various structures. For this reason the obtainment of equations enabling easy computation of such structures is essential for engineering: The problem of bending and elastic buckling stated in the title is solved for structures composed of 1) square or round bars with variable cross-section, 2) lattice elements with variable flexural and torsional rigidities. The slope deflections of the method of displacements, derived in previous paper of the pre- sent authors for bending and buckling of the above elements are made use of. Similar equations are derived for torsion. The examples concern bending and elastic buckling of spatial frame structures and lateral buckling of plane frames with variable bending and torsional rigidity. The slope deflections of the method of displacement derived in the present paper can be applied to the determination of section forces and critical loads in the case of frames of industrial halls, tower and trestle structures. Some bridge elements and various frame structures.